Empowerement of Innovation Food Processing Cassava at Tegal Rejo Siswo Bangun Village - Jaenullah; Nur Laili; Ikhwan Aziz Q; Dedi Setiawan; Habib Shulton Asnawi (International Journal of Community Engagement Payungi, 2022)
The natural resources owned by Tegal Rejo Siswo Bangun Village, include cassava, rubber, rice, and cattle breeding. From these natural resources, the community of Tegal Rejo Siswo Bangun Village are used as a source of income, but they are still limited to selling the produce to the market, not being empowered optimally. The article gave an empowerement of communuty in innovation of food processing based on cassava into cassava pudding, ice tape, and getuk chocolate at Tegal Rejo Siswo Bangun Village, Seputih Banyak Districts. The researchers used ABCD (Asset Based Community Development). The sample was teachers The steeps in giving assistance involve Inkulturasi, Discovery, Design, and Define. The result showed that the community could  give innoavation in adding value of natural resources especially cassava, namely cassava pudding, cassava pudding ice, and Getuk cassava chocolate. The types of products can increase the income of the community of Tegal Rejo Siswo Bangun Village. Through providing training to make product diversification from cassava, this community of Tegal Rejo could help increase family income.